2021
DOI: 10.1038/s41598-021-89179-3
|View full text |Cite
|
Sign up to set email alerts
|

Dementia epidemiology in Hungary based on data from neurological and psychiatric specialty services

Abstract: Hungary has a single-payer health insurance system covering 10 million inhabitants. All medical reports of the in- and outpatient specialist services were collected in the NEUROHUN database. We used ICD-10 codes of Alzheimer’s disease (AD), vascular dementia (VaD), miscellaneous dementia group and mild cognitive impairment (MCI) for the inclusion of the patients. Incidence, prevalence and survival of different dementias and MCI were calculated and analyzed depending on the diagnoses given by neurological or ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Multivariate analysis confirmed that ChEi-filling was an independent significant predictor, even after data were adjusted to age and gender as well. In Hungary, the median survival of patients with all dementias was 3.01 years [ 9 ]; in comparison, ChEi-non-fillers had 2.50 years, while in case of ChEi-fillers it was more than 4 years. There was no significant difference in the length of survival between only ChEi and ChEi plus memantine users, but detailed analysis of memantine use was not the aim of our present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multivariate analysis confirmed that ChEi-filling was an independent significant predictor, even after data were adjusted to age and gender as well. In Hungary, the median survival of patients with all dementias was 3.01 years [ 9 ]; in comparison, ChEi-non-fillers had 2.50 years, while in case of ChEi-fillers it was more than 4 years. There was no significant difference in the length of survival between only ChEi and ChEi plus memantine users, but detailed analysis of memantine use was not the aim of our present study.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of patients and definitions of dementias were the same as in our previous study [ 9 ]. The process is summarized on Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the epidemiology of the disease, conclusions were primarily drawn from coding and literature data. [17,18] Although there were post-mortem studies that found that the proportion of people suffering from vascular dementia in the Hungarian sample was significantly higher than the international rate. [19] Perhaps it is also due to this Hungarian peculiarity that, according to general practitioners, the most common form in Hungary is the vascular type of dementia, and they are not far from the truth with this belief, and perhaps that is why an officially recommended screening protocol is only available for this type, but of course, it can also be the cause of the distorted opinion of general practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50 million people suffer from dementia. This number is expected to triple by 2050 [ 1 , 2 , 3 ]. When dementia develops, it primarily affects memory and other cognitive functions, making daily life activities challenging and affecting orientation in time and space and speech [ 4 ].…”
Section: Introductionmentioning
confidence: 99%